The influence of age and gender on mandibular indices in sample of Libyan population - Bin Hareiz, Asma (Libyan Journal of Dentistry, 2019)
Radiographic Mandibular Indices serve as easy and relatively cheap tools for evaluating bone mineralization. Objectives: To examine the effect of age and gender on three mandibular indices: the panoramic mandibular index (PMI), the mandibular ratio (MR) and the mandibular cortical index (MCI), among Libyan population. Methods: the three indices were measured on 317 digital (OPGs) of adult humans (155 males, 162 females). The sample was divided into six age groups (from 18-25 years. through 56-65 years). The measurements were analyzed for interactions with age and sex, using SPSS (Statistical Package for Social Studies) software version no. 22. The tests employed were two way ANOVA, the unpaired T-test and chi-square test. Results: The mean PMI fluctuated between 0.37 s.d. 0.012 and 0.38 s.d. 0.012.among the sixth age groups. One-way ANOVA statistical test revealed no significant of age on PMI. On the other hand gender variation has effect on PMI, since independent sample t-test disclosed that the difference between the male and female PMI means statistically significant. ANOVA test showed that the means of MR among age groups showed a negative correlation i.e. MR mean declined from 3.01 in 18-25 age group to 2.7 in 55-65 age group. In contrary, the gender showed no effect on MR according two sample t-test at p> 0.05. In regards with MCI, statistical analysis showed that it affected by age that is C1 was decreasing by age while C2 and C3 were increased by age. Using chi square test the result indicated that there is a significant difference among the different age group and the two genders in MCI readings. Conclusion: PMI was influenced significantly by age but minimally by the gender. MR is not affected by gender but has a negative correlation with age. MCI is affected by both age and gender.